The Relevance of Alexander Sutherland Neil's Humanistic Education to the Merdeka Curriculum in Promoting Student Autonomy - Adnan Syah Sitorus; Asril Azhari Hasibuan (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2025)
Education that places student freedom and autonomy at the core of the learning process is becoming increasingly relevant in efforts to shape education that humanizes humanity. This article examines the relevance of Neill's educational thinking to the principles of the Merdeka Curriculum. This research is a literature review using a comparative qualitative approach, aiming to analyze Alexander S. Neill's thoughts on humanistic education and compare them with the Merdeka Curriculum principles, particularly in developing student autonomy. Data was collected through documentation techniques, namely by searching and selecting literature such as books and scientific articles published in relevant national and international journals using keywords such as